Implementation Five-Construct Model to Determine Factors that Affect Customer Satisfaction in The Online Leathercraft Industry - Purnamasari , Dian Indri; Saepudin , Asep; Permadi , Vynska Amalia; Agusdin, Riza Prapascatama (RSF Conference Series: Business, Management and Social Sciences, 2021)
This research uses a five-construct theoretical model as the basis for finding out what factors can satisfy customers in the online leathercraft industry. The questionnaire is based on this model, which is distributed through online channels and social media. There are 691 samples obtained and analyzed by looking at the demographic data and then correlation and regression analysis. The results obtained are that all hypotheses are accepted with factors that can satisfy customers: online shopping experience; external incentives; customer service; and security/privacy; and personal characteristics. For personal characteristics that can be used as factors, namely monthly salary and occupation. These five factors are recommended to be implemented by the online leathercraft industry to satisfy their customers.